Rapid detection of 17β-estradiol based on shaddock peel derived fluorescent aptasensor for forensic examination. (February 2022) - Cheng, Zijia; Ling, Jiang; Zhang, Wenqi; Ding, Yanjun
Highlights: A green synthesis of carbon quantum dots derived from shaddock peel. Rapid and sensitive detection method of 17β-estradiol. Identification of female blood sample by detecting 17β-estradiol. The analytical process could be completed within 10 min. Abstract: 17β-estradiol (E2) detection technique had been shown to a potent method for identification of female blood in forensic practice since it was abundant in the healthy female body. Herein, we developed a fluorescent aptasensor based on carbon quatum dots (CQDs) derived from shaddock peel green synthesis for rapid detection of E2 as a useful auxiliary tool of forensic examination. The CQDs conjugated to the aptamer achieved fluorometric detection of E2 in blood and the blood of healthy female from 12 to 60 years old could be sensitive detected with the limit of detection of 0.025 ng/ml, and the analytical process could be completed within 10 min. The aptasensor was also used to assay E2 in forensic samples including blood and blood stain. In all instances, the results were positive when mixed samples involving female sample. This fluorescent aptasensor was proved to be a green, rapid and sensitive detection method of E2, and it exhibited great potential in discrimination of female samples in forensic practice.